Continuities and changes in Ndebele beadwork: c.1883 to the present - Levy, Diane (My University, 2014)
This dissertation is a study of Ndebele beadwork in terns of continuities and changes in types, styles and functions. In order to explore these concerns, it is relevant to consider the chancing circumstances of the beadwork and, accordingly, both historical and contemporary contexts are discussed. To inform on these themes even further, secondary sources of photographic documentation are examined to provide additional, or to confirm existing information on the art. The Introduction provides a critical analysis of the literature on the beadwork. This literature is discussed in a broad chronology, from the 1920s to the present, considering different socio-political contexts which have influenced the research. In addition to identifying the literature which is useful for an understanding of the beadwork, gaps in the information and methodological weaknesses are defined. These gaps provide pointers for issues and approaches which are adopted in the following chapters. In the course of the Introduction, it becomes apparent that most of the literature has been structured within historical methodologies, resulting in many complex and subtle areas of change being ignored. The Introduction thus defines more open-ended methodologies which are employed in the dissertation. These involve approaching the beadwork from previously unexplored perspectives, including the use of photographic documentation as a potentially rich source of information; an exploration of the relationship between the beadwork and Ndebele history; and the effects of the contemporary commercial markets on the production and functions of the beadwork. In Chapter One, a detailed analysis of photographic documentation of the Ndebele is made. This involves research o n the earliest known documentation by Alfred Martin Duggan- Cronin, dating to 1923 and 1933. This body of work has not been investigated thoroughly in the existing literature, and although highly problematic, it is seen to provide useful visual information on early beadwork. Furthermore, it invites comparison with examples of old and recently made beadwork seen in galleries, shops and private collections. The identification of the types of beadwork seen in these phonographs Is extended into a discussion of the social'' functions of these items. Existing knowledge relating to such functions, as found in the literature, is augmented and extended by information obtained through fieldwork and through studying many beadwork artefacts. In order to identify continuities and changes in the types and styles of the beadwork, more recent photographic documentation is analysed. Reference is made to the images of Constance Stuart Larrabee, who photographed the Ndebele in the 1940s, 1960s and 1980s. Unfortunately, her work proved to be inaccessible, and is thus highlighted as an important area for future research. More detailed visual comparisons are made between the work of Duggan-Cronin and that of Margaret Courtney-Clarke, who documented the Ndebele in the 1980s. Having identified the main types of beadwork and their social functions. Chapter Two explores the possible origins of the beadwork, providing historical context which explains why there may have been a need for this art to develop. Thus the oldest known beadwork is dated to the 1880s, relat ing to the aftermath of the defeat of the Ndebele by the Boers during the Mapoch War of 1883. The circumstances which are described help to explain why the beadwork probably became an important means for the women to express their social status within the group, and furthermore, how it came to communicate ethnic identity to outsiders. By extension, this chapter also raises issues relating to the historical role of women in Ndebele society. An interpretation of the beadwork in an historical context helps to explain why, and how, the social functions of the art developed. This led to questioning to what extent these functions are operative today, and concomitantly, the extent to which 'traditional' types continue to be produced. Chapter Three therefore explores the beadwork in a contemporary context, focusing on the commercial market which has become a major motivation in the production of this art. The extent to which the market has determined changes in the types and styles of the beadwork is addressed, and some of the different kinds of markets, and the way they operate, are defined. Shifts in the women's roles, in the light of their participation in an economic sphere, are also con- sidered. This dissertation ends with a Conclusion, in which the main features of the research, as discussed in the previous sections, are summarised. Pertinent observations, resulting from this study of Ndebele beadwork, are highlighted. A number of questions are raised in considering the future of the beadwork, in terms of its production and functions, recognising that this art has always been, and will continue to be, characterised by continuities and changes.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Arts, 1990.